Customised study companion improves student exam performance: a retrospective study in an undergraduate medicine course (Journal of Applied Learning and Teaching, 2021)
The aims of this study were to retrospectively analyse the relationship between usage of a customised learning tool and medical student performance in an examination, and to solicit student feedback on the learning tool. Learning theories and strategies have long suggested that reducing extraneous load, e.g. by reducing learner attention to multiple information sources, could enhance learning in medicine because of more effective use of cognitive load. A customised learning tool, termed “Study Companion” (Pha1SC), was developed that integrates key analgesic pharmacology contents from several major textbooks. The entire cohort of 231 pre-clinical Medical Year 3 students was offered Pha1SC during the academic year, and 82 of them (“Users”) made use of the learning tool  to various extents. Overall, Users earned higher scores than Non-users on exam questions regardless of their relation to the contents of Pha1SC.  However, Users were more likely to score higher in pharmacology questions than Non-users. More importantly, Users tended to fare better on the Pha1SC-related question independently, regardless of their scores on the question not related to Pha1SC.  Findings in this study support the adoption and refinement of Pha1SC to enhance student learning outcomes in pharmacology.